Osteoporosis: interferon-gamma-mediated bone remodeling in osteoimmunology - Li, Siying; Liu, Gang; Hu, Siwang (Frontiers in Immunology, 2024)
As the world population ages, osteoporosis, the most common disease of bone metabolism, affects more than 200 million people worldwide. The etiology is an imbalance in bone remodeling process resulting in more significant bone resorption than bone remodeling. With the advent of the osteoimmunology field, the immune system's role in skeletal pathologies is gradually being discovered. The cytokine interferon-gamma (IFN-γ), a member of the interferon family, is an important factor in the etiology and treatment of osteoporosis because it mediates bone remodeling. This review starts with bone remodeling process and includes the cellular and key signaling pathways of bone remodeling. The effects of IFN-γ on osteoblasts, osteoclasts, and bone mass are discussed separately, while the overall effects of IFN-γ on primary and secondary osteoporosis are summarized. The net effect of IFN-γ on bone appears to be highly dependent on the environment, dose, concentration, and stage of cellular differentiation. This review focuses on the mechanisms of bone remodeling and bone immunology, with a comprehensive discussion of the relationship between IFN-γ and osteoporosis. Finding the paradoxical balance of IFN-γ in bone immunology and exploring the potential of its clinical application provide new ideas for the clinical treatment of osteoporosis and drug development.